Institutional Performance Of Village Owned Business Entities In South Buton Regency - Zainul Abidin (Jurnal Ad'ministrare, 2021)
Village-Owned Enterprises are village business institutions that are expected to bring progress to the village. This study aims to describe the performance of BUMDes and explain the urgency of the institutional capacity of BUMDes in South Buton Regency especially in Batauga District. This is a new study cause try to explain an institutional performance and show a institutional model at the same time. Data was collected through observation, interviews and document studies. Data were analyzed interactively from data collection to drawing conclusions. The results reveal that the existence of BUMDes has existed since 2016 with problematic BUMDes performance both in-process and results. In terms of the activeness and cooperation process, the existing elements did not go well and many tasks were not carried out. In terms of results, except for the achievement of BUMDes Mandiri Sejahtera in Lampanairi Village, in general it has not achieved the desired results. BUMDes have not been able to develop the local economy both in terms of employment and have not contributed to APBDes revenues. The process improvement and the increase in the expected performance quotient need to be intensified. It is necessary to increase the capacity of BUMDes.